A one pot facile synthesis of Poly(butylene terephthalate)-block-poly(tetramethylene oxide) alternative multiblock copolymers via PROP method. (19th December 2016) - Chen, Jianying; Chen, Dongxue; Huang, Weichun; Yang, Xiaoming; Li, Xiaohong; Tu, Yingfeng; Zhu, Xiulin
Abstract: A novel polycondensation-coupling ring-opening polymerization (PROP) method is utilized to synthesize poly(butylene terephthalate)- block -poly(tetramethylene oxide) alternative multiblock copolymers (PBT- b -PTMO- b -PBT)n via the one pot melt polymerization of cyclic oligo(butylene terephthalate)s (COBTs) and dihydroxy end-functional PTMO (macroinitiator). The proton peaks in 1 H NMR spectra corresponding to each block segments, the segmental ends connecting with different blocks, and copolymer chain ends, are assigned by the 1 H- 1 H gCOSY 2D NMR spectra, respectively. The number-average molecular weights of multiblock copolymers and each segment are revealed by an improved quantitative 1 H NMR spectra. The results show the molecular weights of the multiblock copolymers increase linearly with reaction time, while the molecular weights for each block segment remain the same, following the PROP mechanism, i.e., the ring-opening polymerization of COBTs by PTMO macroinitiator to form PBT- b -PTMO- b -PBT triblock copolymers at the first stage (short and quickly), then coupling with the condensation polymerization of triblock copolymers to form (PBT- b -PTMO- b -PBT)n alternative multiblock copolymers at the second stage. The mechanism is also supported by GPC results. These multiblock copolymers show improved thermal stability compared with PTMO homopolymers. Graphical abstract: Highlights: A polycondensation-coupling ring-opening polymerization (PROP) method is developed. (PBT- b -PTMO- b -PBT)n multiblock copolymers were synthesized by the PROP method. The multiblock copolymers show better thermal stability than PTMO homopolymers.